Design and Performance Testing of Vacuum Induction Furnaces for the Development of Magnesium-Based Biodegradable Implant Materials - Oknovia Susanti; Muhammad Alif Alhadid; Rispandi Rispandi; Alfikri Ikhsan (Jurnal Penelitian Pendidikan IPA, 2026)
Magnesium (Mg) has emerged as a promising biomaterial for implants due to its similarity in physical and mechanical properties to human bone, as well as its ability to degrade safely in the body. However, the main challenges with magnesium are its relatively low mechanical strength and its high tendency to oxidize during the casting process. The use of the Vacuum Induction Casting (VIC) method is crucial to overcome oxidation and porosity issues, resulting in cast products with better integrity. This study aims to design and test the performance of a laboratory-scale vacuum induction furnace for the development of magnesium-based biodegradable implant materials. The furnace was designed using Autodesk Inventor, using a 3.000 W induction module, a water-cooled copper coil, an HA-1 refractory chamber, and a graphite crucible (±52 mL/90 g Mg). Tests showed that the furnace was able to reach an operating temperature of approximately 1.020°C in 2 minutes and 15 seconds, and successfully melted 60 grams of Mg–Gd alloy while the lowest vacuum pressure achieved by the equipment was 0.473 Atm. Rockwell A scale hardness tests yielded average values ​​of 67.1 HRA for Mg–3%Gd and 74.9 HRA for Mg–4%Gd, indicating an increase in hardness with increasing gadolinium content